Management of epidemiological research in a particular region (based on ESSE-RF2 in the Ryazan region) - N. V. Dobrynina; K. A. Moseychuk; N. N. Nikulina; K. G. Pereverzeva; E. V. Filippov (Российский кардиологический журнал, 2019)
Despite the decline in cardiovascular mortality in Russia over the past 15 years, it remains relevant to study the possibilities of its further reducing. And preventive measures of risk factors reducing play the main role. However, before developing preventive measures, it is necessary to study the prevalence and structure of risk factors in a particular region, since Russia is a huge country and each region is different from another. The study of this issue needs large-scale epidemiological studies, the conduct of which is very difficult in organizational terms. This article presents our own experience in successfully organizing a regional phase of epidemiological research.